Window dressing of regulatory metrics: Evidence from repo markets - Claudio Bassi; Markus Behn; Michael Grill; Martin Waibel (European Central Bank (ECB), 2023)
This paper investigates both the magnitude and the drivers of bank window dressing behaviour in euro-denominated repo markets. Using a confidential transaction-level data set, our analysis illustrates that banks engineer an economically sizeable contraction in their repo transactions around regulatory reporting dates. We establish a causal link between these reductions and banks' incentives to window dress and document the role of the leverage ratio and the G-SIB framework as the most relevant drivers of window dressing behaviour. Our findings suggest that regulatory action is warranted to limit banks' ability to window dress.
Keywords: C23; G14; G18; G21; G28; 330; banking regulation; window dressing; repo markets; leverage ratio; G-SIBs